Competition policy and sector-specific regulation for network industries - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2008)
The paper discusses the respective roles of competition policy and sector-specific regulation for industries such as telecommunications, electricity, and gas, in which network infrastructures that are natural monopolies serve as essential facilities for anybody who wants to provide services in downstream markets. Whereas, in the past, such industries tended to be organized as state-owned or state-regulated vertically integrated monopolies, after a fundamental change of paradigm, appropriate governance nowadays is considered to involve downstream competition supported by a state-mandated access provision to the monopoly infrastructures. Following a brief sketch of the paradigm change, the paper enters into a systematic discussion of (i) the comparative advantages and disadvantages of the two policy regimes in enforcing access provision, (ii) the appropriate framework for drawing the line between regulated and unregulated parts of the industry, and (iii) a set of issues that arise when competition policy and to sector-specific regulation apply to a given industry at the same time. The discussion refers to (i) the German experience before 2005 when competition policy was used to regulate access in the energy sector, (ii) the European Directives of 2002, which rely on the concepts of market and significant market power to determine which parts of the industry should be subject to regulation, and (iii) the recent cases in the telecommunications and postal sectors in which European competition law was used to proscribe behaviour that had been accepted by national regulators.
Keywords: K21; K23; L40; L50; 330; Network Industries; Competition Policy; Sector-Specific Regulation; Netzzugang; Wettbewerbspolitik; Netzinfrastruktur; Telekommunikationspolitik; Energiepolitik; Postbeförderung; Regulierung; Deutschland; EU-Staaten